Manajemen Layanan Perpustakaan di MAN 2 Banyuwangi - Retista Tammamy; Hanumatul Hasuna Soraya; Lucky Salama; Febiana Ainul Ilmi; Rofiq Hidayat (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
The aim of this research is to find out how special management services are implemented in libraries carried out by an organization called library ambassador at Madrasah Aliyah Negeri 2 Banyuwangi. Can the planning and organization of special library services increase reading interest among Madrasah Aliyah 2 Banyuwangi students? Therefore, researchers will conduct interviews with library staff, members of library ambassadors, and students of Madrasah Aliyah Negeri 2 Banyuwangi to obtain results and data about library services. The implementation method used is a qualitative descriptive method with data collection through observation, interviews and documentation. The results that will be obtained in this research are that the implementation of special management services at the Madrasah Aliyah Negeri 2 Banyuwangi library through planning, organizing, implementing and controlling can be carried out so that it can fulfill the aim of increasing the students' talents and interests.